Factors That Influence Competence In Improving Employee Performance Through Organizational Commitment As An Intervening Variable In The Personnel Section In Regional Apparatus Organizations Of Riau Islands Province - Syahrianis Syahrianis; Bambang Satriawan; Nolla Puspita Dewi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research examines knowledge, skills, behavior, organizational commitment, and performance in the personnel sections of each regional government organization in the Riau Islands Province. The sample used is non-probability sampling, with a study conducted on 133 personnel department employees from various regional government organizations in the Riau Islands Province. The research method is associative with a quantitative approach, utilizing Partial Least Square (PLS) analysis technique with the SmartPLS Version 3.0 program. The results of this study indicate that there is a significant influence of the knowledge variable on the performance variable, a significant influence of the skills variable on the performance variable, no significant influence of the behavior variable on performance, a significant influence of the organizational commitment variable on the performance variable, a significant influence of the knowledge variable on the organizational commitment variable, a significant influence of the skills variable on the commitment variable, no significant influence of the behavior variable on the organizational commitment variable, a direct influence of the skills variable on the performance variable with organizational commitment as an intervening variable, a direct influence of the knowledge variable on the performance variable with organizational commitment as an intervening variable, and no direct influence of the behavior variable on the performance variable through organizational commitment. The influence of knowledge, skills, and behavior on organizational commitment is 46.2%, with the remaining 53.8% influenced by other variables outside this study. Meanwhile, the influence of knowledge, skills, and behavior on performance is 66.1%, with the remaining 33.9% influenced by other variables outside this study.